2004
DOI: 10.1086/423967
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing Vaccinia on the External Surfaces of 3 Conventional Bandages Applied to Smallpox Vaccination Sites in Primary Vaccinees

Abstract: At 7 days after smallpox vaccination, a peak time for vaccinia shedding, a self-adhesive bandage was as effective as 2 bulkier, less convenient bandages in limiting PCR-detectable virus on the external surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Although the volunteers with gauze and a semipermeable dressing reported significantly less discomfort and had a lower percentage of specimens positive for vaccinia by PCR, the results did not significantly differ from those for the other types of bandage. 7 The present study, in contrast, provides a more detailed comparison of different types of smallpox vaccination site bandages. This study followed up more individuals, stratified study participants by prior vaccination status, and obtained specimens throughout lesion development and healing.…”
Section: Adverse Reactionsmentioning
confidence: 91%
See 3 more Smart Citations
“…Although the volunteers with gauze and a semipermeable dressing reported significantly less discomfort and had a lower percentage of specimens positive for vaccinia by PCR, the results did not significantly differ from those for the other types of bandage. 7 The present study, in contrast, provides a more detailed comparison of different types of smallpox vaccination site bandages. This study followed up more individuals, stratified study participants by prior vaccination status, and obtained specimens throughout lesion development and healing.…”
Section: Adverse Reactionsmentioning
confidence: 91%
“…6 Few investigations have specifically examined retrieval of vaccinia from the surface of vaccination site bandages (Table 2). 4,7,[11][12][13] Before recent vaccination campaigns, studies conducted with recombinant human immunodeficiency virus vaccines in the late 1980s provided the best data on the infectivity of vaccination lesions and the protection provided by standard site dressings. In one such trial in which the vaccination site was covered with gauze and an occlusive bandage, vaccinia was not recovered from the outer bandage surfaces, and no household or sexual contacts developed clinical or serologic evidence of vaccinia exposure.…”
Section: Adverse Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Talbot et al observed that <1% (N = 918) of dressing samples were positive for vaccinia (an initial semipermeable OpSite Post-Op dressing and an outer semipermeable Tegaderm bandage) ( 5 ). In a single-blind randomized trial design, Waibel et al compared the presence of vaccinia virus on the external surface of 3 different types of bandages and noted that the semipermeable membrane with gauze had the smallest proportion of recoverable virus compared with the groups that used a Band-Aid or double gauze with adherent tape ( 6 ). Despite the difference in types of bandages from these studies, the results were remarkably consistent with regard to the limited dissemination of vaccinia virus outside the dressing.…”
mentioning
confidence: 99%